Barefoot and minimalist shoe running - Davis, I. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Barefoot/minimal footwear running is not really a new trend, but rather dates back to our beginnings. Up until 50 years ago, runners ran in very minimal shoes, and up until 40 years ago, there were no reports of running injuries in the literature. One hypothesis for the increase in running injuries has been the addition of cushioning in the running shoe that occurred in the early 1960s. This cushioning makes it comfortable to land on ones. heels and likely accounts for the 89% of runners in cushioned shoes that are rearfoot strikers. Recent reports suggest that the majority of barefoot and minimally shod runners do not land on their heels. Interestingly, it has also been reported that children, two years of age, land with a slightly plantarflexed foot during shod running. However, by the time they are four, they are heelstriking with nearly 10 deg. of dorsiflexion. It is well-recognized that heelstriking is associated with an impact transient not typically present with a forefoot strike pattern. This impact transient has been associated with common running-related injuries. Modern shoes have also become more supportive. However, recent evidence suggests removing some of this support results in foot strengthening, which may lead to reduced risk of common injuries such as plantar fasciitis. Clearly the technological advancements in footwear have not reduced injuries as up to 79% of shod runners still get injured in a given year. This suggests a paradigm shift in our thinking may be needed. Prospective RCT studies are clearly warranted.